Peachy Scarf Sdn. Bhd / Noor Amira Mohd Ansari - Mohd Ansari, Noor Amira (2021)
This study is for the study of business resources conducted by students. Students have created a social media account on Facebook to be promoting sales products on learning matters. Therefore, students were given an assessment to create any posts during this 14 -week learning. Students can engage with a variety of information obtained on the platform used. After completing the assessment given, students need to make a report on the campaign work that has been done. Here, it needs to include any evidence of the post on Facebook and also Go- Ecommerce registration.